1996
DOI: 10.1207/s15324826an0303&4_12
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological findings in adult attention deficit disorder: a pilot study

Abstract: Relatively little is known about neuropsychological deficits in adults with Attention Deficit Disorder (ADD). This paper presents data for a consecutive series of 11 adults diagnosed as having adult ADD. The sample had a mean age of 33 4 years (range=22-56) and mean education of 15 years (range=8-19) and included 5 women and 6 men All were Caucasians. A neuropsychological test battery was administered. The results suggested few neuropsychological deficits except in the initial acquisition of verbal information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Neuroimaging studies using magnetic resonance imaging (MRI) and positron emission tomography (PET) (Bush et al, 1999;Casey et al, 1997;Castellanos et al, 1996;Filipek et al, 1997;Hesslinger et al, 2002;Hynd et al, 1993;Lou, Henriksen, & Bruhn, 1984;Rubia et al 1999;Vaidya et al, 1998) revealed that anomalies of prefrontal cortical regions and the basal ganglia in particular represent neuroanatomical substrates of ADHD. Furthermore, neuropsychological studies using standardized psychometric procedures demonstrated marked disturbances of adult patients with ADHD in a variety of executive functions, including shifting, working memory, impulsivity and verbal fluency (Corbett & Stanczak, 1999;Dinn et al, 2001;Downey et al, 1997;Hopkins et al, 1979;Horton, 1996;Kovner et al, 1998;Taylor & Miller, 1997).…”
Section: Clustering and Switching In Adult Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies using magnetic resonance imaging (MRI) and positron emission tomography (PET) (Bush et al, 1999;Casey et al, 1997;Castellanos et al, 1996;Filipek et al, 1997;Hesslinger et al, 2002;Hynd et al, 1993;Lou, Henriksen, & Bruhn, 1984;Rubia et al 1999;Vaidya et al, 1998) revealed that anomalies of prefrontal cortical regions and the basal ganglia in particular represent neuroanatomical substrates of ADHD. Furthermore, neuropsychological studies using standardized psychometric procedures demonstrated marked disturbances of adult patients with ADHD in a variety of executive functions, including shifting, working memory, impulsivity and verbal fluency (Corbett & Stanczak, 1999;Dinn et al, 2001;Downey et al, 1997;Hopkins et al, 1979;Horton, 1996;Kovner et al, 1998;Taylor & Miller, 1997).…”
Section: Clustering and Switching In Adult Adhdmentioning
confidence: 99%
“…Tasks assessing aspects of executive functions have been shown to be particularly sensitive measures for the detection of cognitive impairments of adult patients with ADHD. While concept formation, planning, and problem-solving abilities have been shown to be undisturbed in these patients, impairments of attention, working memory, impulsivity, shifting and divergent thinking have been observed (Corbett & Stanczak, 1999;Dinn, Robbins, & Harris, 2001;Downey, Stelson, Pomerleau, & Giordani, 1997;Gansler et al, 1998;Holdnack, Moberg, Arnold, Gur, & Gur, 1995;Hopkins, Perlman, Hechtman, & Weiss, 1979;Horton, 1996;Katz, Wood, Goldstein, Auchenbach, & Geckle, 1998;Kovner et al, 1998;Mattes, Boswell, & Oliver, 1984;Matochik, Rumsey, Zametkin, Hamburger, & Cohen, 1996;Riordan et al, 1999;Seidman, Biederman, Weber, Hatch, & Faraone, 1998;Silverstein, Como, Palumbo, West, & Osborn, 1995;Taylor & Miller, 1997;Weyandt, Rice, Linterman, Mitzlaff, & Emert, 1998).…”
mentioning
confidence: 99%
“…Psychometric assessments have demonstrated that, in comparison to healthy adults, adult patients with ADHD display deficiencies of various functions which have been associated with the frontal lobes. These include attention, working memory, concept formation, impulsivity, and shifting (Arcia & Gualtieri, 1994;Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005;Corbett & Stanczak, 1999;Dinn, Robbins, & Harris, 2001;Epstein, Johnson, Varia, & Conners, 2001;Holdnack, Moberg, Arnold, Gur, & Gur, 1995;Hollingsworth, McAuliffe, & Knowlton, 2001;Hopkins, Perlman, Hechtman, & Weiss, 1979;Horton, 1996;Johnson et al, 2001;Klee, Garfinkel, & Beauchesne, 1986;Kovner et al, 1998;Lovejoy et al, 1999;Silverstein, Como, Palumbo, West, & Osborn, 1995;Tucha et al, 2006;Walker, Shores, Trollor, Lee, & Sachdev, 2000). However, problem-solving abilities of adults with ADHD have not been examined in detail.…”
mentioning
confidence: 99%